Corporate Directors as a Resource to the Firm: Evidence from Saudi Arabia - Mubarak , Wadhaah; Mubarak , Ayth (The Arab Journal of Administration, 2023)
Despite the increasing interest on the board of directors as one of the most effective tools for corporate governance, it is not clear how these directors function and what are their roles. This research aims to study the resource role of independent board directors (IDs) within the Saudi context. To achieve this goal, 29 semi-structured interviews were conducted. The results indicate that there is a consensus on the appropriateness of IDs performing this role, with some opposing views that were discussed. Further, the results points to three channels through which IDs perform this role. These channels are utilizing their relationships to overcome external threats, contributing to the formation of long-lasting alliances, and facilitating ceasing external opportunities. Moreover, the findings indicate that IDs are effective in this role, and that regulations, large shareholders, management, personal characteristic of the IDs, and their compensations influence this effectiveness. Overall, these findings enrich corporate governance literature, and provide corporations and regulators with a deep insight into the resource role of IDs in Saudi Arabia, while recommending putting further emphasis on the importance of considering this role when selecting directors.